2022
DOI: 10.1016/j.oftale.2022.01.001
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 pandemic: Impact on the rate of viral conjunctivitis

Abstract: Objective The COVID-19 pandemic led Spain to order a state of alert with the cessation of non-essential activities on 14 March 2020, and to implement public health interventions (such as home confinement) and other health recommendations to prevent the spread of the SARS-CoV-2 virus (hand washing and the obligation to wear face-masks). These factors could have influenced the rate of viral conjunctivitis. Method In this retrospective, noninterventional, descriptive study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
2
4
0
Order By: Relevance
“…In this report, it was found that the general prevalence of conjunctivitis was affected by the COVID-19 pandemic, where a significant reduction in cases of conjunctivitis can be seen when comparing the prepandemic year with the first year of the pandemic, which is consistent with other studies [12,13]. Thus, for example, Conde et al [12] documented a 48.5% reduction in cases of viral conjunctivitis in a hospital institution in Spain, while in the USA, Lavista et al [13] identified a 37.3% reduction in patients with non-allergic conjunctivitis. These changes may be due to social distancing, isolation, travel restrictions, closure of colleges and universities, less use of health services for conditions other than COVID-19, as well as a greater emphasis on hygiene and the use of personal protection elements [12,13].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In this report, it was found that the general prevalence of conjunctivitis was affected by the COVID-19 pandemic, where a significant reduction in cases of conjunctivitis can be seen when comparing the prepandemic year with the first year of the pandemic, which is consistent with other studies [12,13]. Thus, for example, Conde et al [12] documented a 48.5% reduction in cases of viral conjunctivitis in a hospital institution in Spain, while in the USA, Lavista et al [13] identified a 37.3% reduction in patients with non-allergic conjunctivitis. These changes may be due to social distancing, isolation, travel restrictions, closure of colleges and universities, less use of health services for conditions other than COVID-19, as well as a greater emphasis on hygiene and the use of personal protection elements [12,13].…”
Section: Discussionsupporting
confidence: 91%
“…The prevalence of conjunctivitis varies according to the etiology and can be influenced by the patient's age, sex, as well as by the seasons of the year [1,11]. In this report, it was found that the general prevalence of conjunctivitis was affected by the COVID-19 pandemic, where a significant reduction in cases of conjunctivitis can be seen when comparing the prepandemic year with the first year of the pandemic, which is consistent with other studies [12,13]. Thus, for example, Conde et al [12] documented a 48.5% reduction in cases of viral conjunctivitis in a hospital institution in Spain, while in the USA, Lavista et al [13] identified a 37.3% reduction in patients with non-allergic conjunctivitis.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Conde Bachiller et al, in their study, found a significant reduction in conjunctivitis, with the most significant decrease in viral conjunctivitis cases during COVID-19. 67 …”
Section: Positive Effects Of Covid-19mentioning
confidence: 99%
“…4,5 Public health measures aimed at reducing transmission of COVID-19 have been associated with a reduction in incidence of respiratory viruses, as well as the number of emergency department (ED) encounters for viral conjunctivitis. [6][7][8] The mean number of weekly ED visits significantly decreased with the onset of the COVID-19 pandemic, as the landscape and utilization of healthcare in the United States drastically changed. 9 The majority of pre-pandemic ED visits (75%) were characterized as non-emergent, allowing for a substantial decline in ED presentation as deterrence from potential COVID-19 exposure grew.…”
Section: Introductionmentioning
confidence: 99%